2001
DOI: 10.1109/81.904887
|View full text |Cite
|
Sign up to set email alerts
|

On the topology and number of operating points of MOSFET circuits

Abstract: This paper reviews previous theory regarding the existence and uniqueness of dc operating points possessed by bipolar transistor circuits and applies it to MOSFET circuits. Two primary results are presented. First, it is shown that certain previous topological results regarding the uniqueness of dc operating points for bipolar junction transistor and JFET circuits do not strictly hold for MOSFET circuits. Second, a two-transistor MOSFET circuit that possesses five operating points is presented. This circuit is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…A different, geometric approach stems from the work of Brayton and Moser [45,46]; later results in this direction can be found in [47][48][49][50][51][52][53]. Other developments in the last two decades have concerned singularities in DAE models [10,11,29,30,33], general circuit modelling [14, 15, 17-19, 31, 39, 52-56], and qualitative results for certain circuit families [27,28,57,58], besides of course numerical aspects.…”
Section: Qualitative Results Based On State-space Modelsmentioning
confidence: 98%
“…A different, geometric approach stems from the work of Brayton and Moser [45,46]; later results in this direction can be found in [47][48][49][50][51][52][53]. Other developments in the last two decades have concerned singularities in DAE models [10,11,29,30,33], general circuit modelling [14, 15, 17-19, 31, 39, 52-56], and qualitative results for certain circuit families [27,28,57,58], besides of course numerical aspects.…”
Section: Qualitative Results Based On State-space Modelsmentioning
confidence: 98%
“…A feedback structure is identified by setting all independent source values to zero, by open-circuiting and/or short-circuiting resistors, and by replacing all but two of the transistors by a pair of open and/or short circuits. The extension of the topological criteria to more general three-terminal devices (including FETs) [67], circuits employing Ebers-Moll-modeled transistors having variable current-gains [18], and metal-oxide-semiconductor field-effect transistor (MOSFET) circuits [15] have been also established.…”
Section: Number Of DC Operating Pointsmentioning
confidence: 99%
“…In [10], it was shown that the simple nMOS latch circuit shown in Fig. 1 can be made to possess five operating points, three of which are stable.…”
Section: Theoretical Backgroundmentioning
confidence: 99%